Implementing Web Liveworksheet-Based Scientific Critical Creative Thinking Model to Improve Students' Thinking Skills - Pia Asti Puspasari; Rusmansyah Rusmansyah; Muhsinah Annisa; Arief Ertha Kusuma; Asmi Rusmanyanti; Nasrullah Nasrullah; Tien Tien Lee; Nurlaila Hayati (Journal of Mathematics Science and Computer Education, 2026)
This study aimed to investigate the effect of the Web Liveworksheet-Based SCCrT Model on students’ (1) creative thinking skills, (2) critical thinking skills, and (3) responses toward the implementation of the model in learning the basic laws of chemistry. The study employed a pre-experimental method using a one-group pretest-posttest design. The participants consisted of 35 students. Data were collected through creative and critical thinking tests and analyzed descriptively. The findings revealed that implementing the SCCrT Model improved students’ creative thinking skills, as indicated by an increase in the mean score from 23.44 to 71.70. In addition, students’ critical thinking skills also improved, with the mean score increasing from 32.71 to 71.14. Furthermore, students demonstrated good responses toward the implementation of the SCCrT model, with 74.51% expressing positive responses. These findings indicate that the SCCrT Model has the potential to improve students’ creative and critical thinking skills in learning the basic laws of chemistry topic.